Experimental study on shear behavior of activated fly ash concrete beams - George, Sunilaa; Thenmozhi, R.; Magudeswaran, P. N. (Journal of Structural Engineering, 2025)
The use of supplementary cementitious materials (SCM) has dramatically increased along with the development of the concrete industry. The large scale production of cement is adding to environmental problems in one hand and depleting the natural resources on the other. This threat to the ecology has lead researchers to utilize the industrial bi-products as SCM in making concrete Eco-friendly. The use of fly ash as a cement replacement material increases the long-term strength and durability of concrete. Despite these great benefits, the use of fly ash is limited due to the low early strength development of fly ash concrete with normal water cement ratio. To eliminate this problem, many studies have been conducted on accelerating the pozzolanic properties of fly ash. Many methods are in use to activate fly ash; chemical activation is one of the easiest. This study is aimed at replacing the cement in concrete with chemically activated fly ash to investigate the shear behavior of concrete beams. Various replacements used in the study are 10%, 20%, 30%, 40%,50% and 60% with water binder ratio of 0.5 and the results from these studies are compared with fly ash concrete beams and control specimens.